Back Cover: Few‐Layer Antimonene by Liquid‐Phase Exfoliation (Angew. Chem. Int. Ed. 46/2016). Issue 46 (11th October 2016) - Gibaja, Carlos; Rodriguez‐San‐Miguel, David; Ares, Pablo; Gómez‐Herrero, Julio; Varela, Maria; Gillen, Roland; Maultzsch, Janina; Hauke, Frank; Hirsch, Andreas; Abellán, Gonzalo; Zamora, Félix
Abstract : Sonication‐assisted liquid‐phase exfoliation of antimony crystals gives rise to very stable suspensions of high‐quality single/few‐layer antimonene, as shown by G. Abellán, F. Zamora, and co‐workers in their Communication onpage 14345 ff. A new nanomaterial was thus produced that will facilitate the development of a broad range of applications based on antimonene, including electronics and optoelectronics.